2016
DOI: 10.5505/sakaryamedj.2016.00377
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Levels and Related Factors of Family Doctors Who Work At Family Health Centers in Sakarya Province

Abstract: Amaç: Bu çalışmada, Sakarya il merkezi ve ilçelerinde aile sağlığı merkezlerinde çalışan aile hekimlerinin tükenmişlik düzeylerini ve bunların çeşitli değişkenlerle ilişkilerini saptamak amaçlanmıştır. Yöntem: 1 Şubat-28 Şubat 2014 tarihleri arasında yürütülen kesitsel tipteki bu çalışmada Sakarya'da aile hekimi olarak çalışan 258 hekimden 157'sine (%60.8) ulaşılmıştır. Veriler, Maslach Tükenmişlik Ölçeği ve araştırmacılar tarafından hazırlanan standart bir anket formu kullanılarak toplanmıştır. İstatistiksel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
2
1
0
5
Order By: Relevance
“…Our study determined low mean emotional exhaustion, depersonalization, and personal accomplishment scores in physicians working in primary health care institutions in Erzurum. Similar results to ours were reported in a study of family physicians in Sakarya [12]. Baykan et al [13] reported lower mean emotional exhaustion and depersonalization and higher personal accomplishment scores compared to our findings in their study involving family physicians.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study determined low mean emotional exhaustion, depersonalization, and personal accomplishment scores in physicians working in primary health care institutions in Erzurum. Similar results to ours were reported in a study of family physicians in Sakarya [12]. Baykan et al [13] reported lower mean emotional exhaustion and depersonalization and higher personal accomplishment scores compared to our findings in their study involving family physicians.…”
Section: Discussionsupporting
confidence: 92%
“…Single subjects in our study scored higher regarding depersonalization than married participants. Şerik et al [12] reported similar findings to ours. We may, therefore, conclude that positive, mutual sharing among married subjects means that they are less exposed to depersonalization.…”
Section: Discussionsupporting
confidence: 90%
“…At the end of the research, family physicians’ burnout levels were low. Similarly, Serik et al26 found that burnout levels were generally low in the study conducted with 157 family physicians working in family health centers in Sakarya province.…”
Section: Discussionmentioning
confidence: 76%
“…Aile hekimleri ile yapılan bir çalışmada katılımcılar iş yükü fazlalığı, gereksiz iş yükü, yetersiz fiziksel koşullarla ilgili sorunların yanında hasta kaynaklı tutum ve davranışlar ile ilgili sorunlar yaşadıklarını belirtmişlerdir. Aynı çalışmada katılımcıların %23,9'u hasta ve yakınları tarafından uygulanan olumsuz bir davranışla karşılaşmış ve bu durumun tükenmişlik ve duyarsızlaşmayı artırdığı belirlenmiştir (24). Bu araştırmada sağlık çalışanlarının %33,3'ü psikolojik şiddete maruz kaldıklarını belirtmişlerdir.…”
Section: Sağlık Durumlarıunclassified